SISTEM INFORMASI REKAM MEDIS PUSKESMAS BERBASIS WEB - Ismiyarti, Wilia; Juliani, Eka Juliani2 (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2023)
Abstract Lopok Health Center is one of the health centers in Sumbawa district. The processing of medical record data at the Lopok health center is still done manually. All medical record data is still in the form of paper that is stacked and stored on shelves, so when a patient's medical record data is needed it will take quite a long time to find a place to store it. In addition, this is also vulnerable to loss or damage to files. The software development method used is the waterfall method, the programming language uses PHP and the framework uses Codeigneter, the database uses MySQL, the design uses UML, and is tested by blackbox testing. The purpose of this research is to build a web-based puskesmas medical record information system that can assist the puskesmas in managing medical record data so that services can be made faster and more accurate. The result of this research is a web-based medical record information system for the Lopok Health Center.Â Keywords: Â Information Systems, Medical Records, PHP, UML, WaterfallÂ DAFTAR PUSTAKAAhmad, A., & Ferdinandus Lidang Witi. (2021). Perancangan dan Implementasi Sistem Informasi Rekam Medis (Studi Kasus: Puskesmas Onekore). SATESI: Jurnal Sains Teknologi Dan Sistem Informasi, 1(2), 61â€“70. https://doi.org/10.54259/satesi.v1i2.26 Â Aldo, D., & Putra, N. (2020). Sistem Pendukung Keputusan (SPK) (Kupas Tuntas Metode Multifaktor Evaluation Process). SINT Publishing. Â Anggraeni, R. (2019). Mutu Pelayanan Kefarmasian Di Puskesmas. Deepublish. Anita, B., Febriawati, H., & Yandrizal. (2019). Puskesmas Dan Jaminan Kesehatan Nasional. Deepublish. Â Batubara, & Husein, H. (2017). Teknologi Informasi dan Komunikasi (TIK). Deepublish. Â Destriana, R., Husain, S. M., Handayani, N., & Siswanto, A. T. P. (2021). Diagram UML Dalam Membuat Aplikasi Android Firebase â€œStudi Kasus Aplikasi Bank Sampah.â€ Deepublish. Â Enterprise, J. (2018). HTML, PHP, dan MySQL untuk Pemula. Elex Media Komputindo. Â Fitri, R. (2020). Pemrograman Basis Data Menggunakan MySQL. Deepublish. Â Indrawan, G. (2021). Database MySQL dengan Pemograman PHP - Rajawali Pers. PT. RajaGrafindo Persada. Â Krisbiantoro, D., & Abdaâ€™u, P. D. (2021). Dasar Pemrograman Web dengan bahasa HTML, PHP, dan Database MySQL. Zahira Media Publisher. Â Mathar, I. (2018). Manajemen Informasi Kesehatan: Pengelolaan Dokumen Rekam Medis. Deepublish. Â Nabuasa, Y. Y. (2021). Analisis Dan Perancangan Sistem Informasi Rekam Medis Sebagai Sarana Pelayanan Kesehatan Pada Puskesmas OESAPA Kota Kupang. Applied Information System and Management (AISM), 2(1), 40â€“46. https://doi.org/10.15408/aism.v2i1.20209 Â Ningsih, S. R., & dkk. (2022). Perancangan Basis Data (R. W. Janner Simarmata (ed.)). Yayasan Kita Menulis. Â Nisak, & Khoirun, U. (2021). Pengantar Rekam Medis Dan Manajemen Informasi Kesehatan (S. B. Sartika (ed.)). umikhoirun. Â Nugroho, B., Fitriasih, S. H., & Widada, B. (2020). Sistem Informasi Rekam Medis Di Puskesmas Masaran I Sragen. Great Day, 3(2), 49â€“56. http://bit.ly/2jr3AXt Â Permana, P. I., & Purnomo, A. N. (2021). Pemrograman Web dan Perangkat Bergerak SMK/MAK Kelas XI. Gramedia Widiasarana indonesia. Â Prassetio, T., & Rofiq, N. N. (2022). Perancangan Sistem Informasi Rekam medis Rawat Jalan Pada Rumah Sakit Mayapada Tanggerang Menggunakan Metode Prototype Berbasi Web. 1(04), 373â€“379.Â Putratama, S., & Vidiandry. (2018). Pemrograman Web dengan Menggunakan PHP dan Framework Codeigniter. Deepublish. Â Rachmadi, T. (2020). Sistem Basis Data. TIGA Ebook. Â Ramadhani, A. R., Zaidiah, A., & Astriratma, R. (2020). Perancangan Aplikasi Sistem Informasi Rekam Medis Pada Puskesmas Majasari Pandeglang Berbasis Web. Senamika, 73â€“84. http://repository.unama.ac.id/id/eprint/1201 Â Romindo, R., & dkk. (2021). Sistem Informasi (J. Simarmata (ed.)). Yayasan Kita Menulis. Â Rosyidah, M., & Fijra, R. (2021). Metode Penelitian. Deepublish. Â Salim, H. (2019). Penelitian Pendidikan: Metode, Pendekatan, dan Jenis. Kencana. Â Santi, & Hartami, I. (2020). Analisa Perancangan Sistem (M. Nasrudin (ed.)). Penerbit NEM. Â Sanubari, T., Prianto, C., & Riza, N. (2020). Odol (one desa one product unggulan online) penerapan metode Naive Bayes pada pengembangan aplikasi e-commerce menggunakan Codeigniter. Kreatif. Â Suendri. (2021). Buku Ajar Pemrograman Berbasis Web. Media Sains Indonesia. Â Yendrianof, D., & dkk. (2022). Analisis dan Perancangan Sistem Informasi (A.Karim (ed.)). Yayasan Kita Menulis.